Ludwik Hirszfeld: A pioneer of transfusion and immunology during the world wars and beyond. Issue 4 (7th November 2021) - Czerwinski, Marcin; Kaczmarek, Radoslaw; Glensk, Urszula
Abstract: Ludwik Hirszfeld (1884–1954) was a Polish physician, immunologist and microbiologist. Together with Emil von Dungern, he showed that blood groups are heritable traits and established the terminology of the ABO blood group system. He discovered A1 and A2 blood groups, and showed for the first time, in a large‐scale population study, that blood group frequency differs between populations. During World War I, he volunteered as an army physician. In the interwar period, he helped to create the National Institute of Hygiene in Warsaw and was instrumental in developing transfusion centres in Poland. During World War II, which he barely survived, he co‐organized secret medical courses in the Warsaw Ghetto and played a major role in containing the typhus epidemic that ran rampant there since 1941. After the war, he was the first in Poland to put the theory of serological conflict between mother and foetus into clinical practice, saving the lives of almost 200 children by introducing exchange transfusions.